A silent acute abdomen in a patient with spinal cord injury. (27th March 2013) - Malhotra, Rishi; Ee, Gerard; Pang, Si Ying; Kumar, Naresh
Abstract : A 52-year-old man with cervical spondylosis sustained a hyperextension injury to the neck and subsequently developed central cord syndrome after 2 weeks. The diagnosis was confirmed clinically and on MRI. During the admission he was febrile from Streptococcus anginosus bacteraemia from a gum infection and was started on penicillin. This resulted in pseudomembranous colitis with abdominal distension and bloody diarrhoea but a lack of expected abdominal complaints. Unfortunately his neurology deteriorated and a repeat MRI showed a discitis at C5–C7 which required a 2-level discectomy, debridement and instrumented fusion. Owing to his spinal cord injury, an abdominal perforation was initially missed owing to the lack of clinical features of an acute abdomen. He underwent a right hemi-colectomy for ascending colon perforation and eventually made a good recovery and was discharged to a spinal rehabilitation unit. By one year follow-up he had returned to full neurological function.